Snowfall, Temperature, and the Risk of Death From Myocardial Infarction: A Case-Crossover Study. Issue 8 (4th March 2020) - Gan, Wen Qi; Henderson, Sarah B; Mckee, Geoffrey; Yuchi, Weiran; McLean, Kathleen E; Hong, Kris Y; Auger, Nathalie; Kosatsky, Tom
Abstract: Previous research has associated snowfall with risk of myocardial infarction (MI). Most studies have been conducted in regions with harsh winters; it remains unclear whether snowfall is associated with risk of MI in regions with milder or more varied climates. A case-crossover design was used to investigate the association between snowfall and death from MI in British Columbia, Canada. Deaths from MI among British Columbia residents between October 15 and March 31 from 2009 to 2017 were identified. The day of each death from MI was treated as the case day, and each case day was matched to control days drawn from the same day of the week during the same month. Daily snowfall amount was assigned to case and control days at the residential address, using weather stations within 15 km of the residence and 100 m in elevation. In total, 3, 300 MI case days were matched to 10, 441 control days. Compared with days that had no snowfall, odds of death from MI increased 34% (95% confidence interval: 0%, 80%) on days with heavy snowfall (≥5 cm). In stratified analysis of deaths from MI as a function of both maximum temperature and snowfall, risk was significantly increased on snowfall days when the temperature was warmer.